AB0786 IMPACT OF PSORIASIS SEVERITY ON HEALTH-RELATED QUALITY OF LIFE IN EARLY PSORIATIC ARTHRITIS: RESULTS FROM REAL WORLD DATA, THE DEPAR STUDY. (13th June 2020) - Kasiem, F. R.; Kok, M. R.; Tchetverikov, I.; Wervers, K.; Hazes, J.; Luime, J.; Vis, M.
Abstract : Background: Psoriasis is an important feature of psoriatic arthritis (PsA). Psoriasis itself is known to have a significant impact on Health-related Quality of life (HRQoL) 1, however its role within PsA is less well understood. In daily practice, assessment of psoriasis may not always be a priority for rheumatologists, having been trained to focus on articular involvement. In order to assess whether psoriasis deserves more attention from rheumatologists, the aim of this study is to evaluate the influence of psoriasis on HRQoL in early PsA patients. Objectives: To describe the evolution of psoriasis severity during the first year of follow up in patients with early PsA and to evaluate the impact of psoriasis severity on HRQoL. Methods: Real world data were used from the Dutch south west Psoriatic Arthritis cohort (DEPAR) study, consisting of newly diagnosed PsA patients included between July 2013 and February 2019. Psoriasis severity was assessed using the Psoriasis Area and Severity Index (PASI) and categorized in: no psoriasis (PASI 0), mild psoriasis (PASI<7), moderate psoriasis (PASI 7-12) and severe psoriasis (PASI>12). Musculoskeletal disease severity was measured with the Disease Activity in PSoriatic Arthritis (DAPSA) score as contrast for psoriasis severity. DAPSA was categorized in: remission (REM[DAPSA≤4]), low disease activity (LDA[DAPSA≤14]), moderate disease activity (MDA[DAPSA≤28]) and high disease activity (HDA[DAPSA>28]). 2 General HRQoL was assesed with the Short-Form 36 (SF-36[Physical component scale and Mental component scale]). Skin-specific HRQoL was measured with the Skindex-17 (psychosocial scale and symptoms scale). Results: In total, 435 patients were included. Mean (sd) age was 49.7 (13.4) years and 53% (n=229) was male. Psoriasis severity does not fluctuate much over the course of the first year and the majority of patients had mild psoriasis (Figure 1 ). HRQoL worsened with increasing psoriasis severity, when measured by the Skindex17. This reduction in HRQoL was not seen when measured with the SF-36 (Figure 2 ). Conclusion: In early PsA patients, psoriasis severity is mostly mild, but considerably impacts HRQoL when measured using a skin specific questionnaire. For optimal management of PsA patients, we therefore recommend rheumatologists to additionally acquire information on the degree of psoriatic involvement. In our opinion, this information is valuable for the adequate assessment of HRQoL. References: [1]Strober B, Greenberg JD, Karki C, Mason M, Guo N, Hur P, et al. Impact of psoriasis severity on patient-reported clinical symptoms, health-related quality of life and work productivity among US patients: real-world data from the Corrona Psoriasis Registry. BMJ Open. 2019;9(4):e027535. [2]Schoels MM, Aletaha D, Alasti F, Smolen JS. Disease activity in psoriatic arthritis (PsA): defining remission and treatment success using the DAPSA score. Ann Rheum Dis. 2016;75(5):811-8. Disclosure of Interests: Fazira R. Kasiem: None declared, Marc R Kok Grant/research support from: BMS and Novartis, Consultant of: Novartis and Galapagos, Ilja Tchetverikov: None declared, Kim Wervers: None declared, Johanna Hazes: None declared, Jolanda Luime: None declared, Marijn Vis Grant/research support from: Novartis, Pfizer – grant/research support, Consultant of: AbbVie, Celgene Corporation, Eli Lilly, Novartis, Pfizer – consultant